TRIPS and Bilateral Investment Treaties: the need to find a harmony in your application - Lentner, Gabriel M.; Proaño, Sheila E. (Iuris Dictio, 2017)
This paper analyzes the current international standards for the protection of intellectual property rights by international investment agreements with particular emphasis on bilateral investment treaties (BITs) and how these relate to TRIPS. It demonstrates that international standards for the protection of intellectual property rights after the entry into force of the TRIPS Agreement remain inconsistent. The TRIPS-plus standards as included in BITs erode the flexibilities provided for in the TRIPS Agreement. In doing so, this paper raises the necessity of clarifying the international legal framework in this respect, in order to allow these two bodies of law to coexist in a harmonious and coherent manner.